Overview of apprenticeship systems and issues : ILO contribution to the G20 Task Force on Employment - Steedman, Hilary [Verfasser] (ILO, 2012)
"Quality apprenticeships based on robust social dialogue and public-private partnerships help young people overcome the work-inexperience trap that blocks their transition from education to employment. The ILO has identified key success factors around which quality apprenticeship programmes bridge training to productive and decent work. Better and more broadly available apprenticeships, and other training opportunities, can reduce youth unemployment and poverty when combined with national efforts to spur job growth. This paper provides an overview of current apprenticeship programmes and practices in a limited number of countries. The evidence and lessons drawn from their experience provide both motivation and practical recommendations for making apprenticeship a more attractive and a more efficient pathway to productive and decent jobs for more young people." (Textauszug; BIBB-Doku)
Keywords: S System beruflicher Bildung; Berufsbildungssystem; Internationaler Vergleich; Berufsausbildung; Jugendarbeitslosigkeit; Berufsbildungspolitik; Sozialpartner